Development of Improved Wide Temperature Range Arctic Engine Oil (OEA-30). - Frame, Edwin A. (1996)
The technical feasibility of developing an improved, multifunctional arctic engine oil for U.S. military ground mobility equipment was investigated. The concept was proven feasible, and the new oil was designated as OEA-30. The current arctic engine oil (MIL-L-46167B) is qualified at 22 percent derated conditions in a two-cycle diesel engine test. OEA-30 has exceptional two-cycle diesel engine performance at full engine output and can be operated beyond the 5 deg C (40 deg F) maximum ambient temperature limit of the current arctic oil. Multifunctional requirements of OEA-30 were achieved by including selected portions of Allison Transmission Division C-4 and Caterpillar TO-4 specifications. The most promising OEA-30 candidate was reformulated to American Petroleum Institute (API) CG-4 performance level and will be further evaluated in a follow-on program.